Alternative herbicides to paraquat in pre-harvest desiccation of soybean plants (Revista de Ciências Agroveterinárias, 2024)
Diquat, glufosinate and the combination of the latter with carfentrazone or saflufenacil are believed to be as effective for pre-harvest desiccation of soybean plants as paraquat. This work was developed with the objective of evaluating the efficacy of paraquat, diquat, and glufosinate alone or at mixtures of carfentrazone or saflufenacil in pre-harvest desiccation of soybean. Soybean defoliation, maturity and yield were evaluated. Similar efficacy was observed between glufosinate and paraquat in soybean defoliation and maturity, in addition to a greater flexibility of use, in which it could be an anticipator and standardizing agent of the harvest. The application of diquat (200 g of active ingredient [a.i.] ha-1), paraquat (200 g a.i. ha-1) or glufosinate (400 or 500 g a.i. ha-1) was effective for pre-harvest desiccation of soybean at the R7.2 stage. As well, it was observed promising results for application of glufosinate + saflufenacil (300 + 24.5 g a.i. ha-1), glufosinate + carfentrazone (200 + 25 g a.i. ha-1), glufosinate + saflufenacil (200 + 35 g a.i. ha-1). Diquat and glufosinate can replace paraquat in pre-harvest desiccation of soybean plants, and glufosinate also provide greater management flexibility, in anticipating the harvest.
Keywords: diquat; glufosinate; saflufenacil; carfentrazone; defoliation; yield